Towards the interaction between large solutes in a fluid of small hard spheres - Henderson, D.; Wasan, D.T.; Trokhymchuk, A. (Condensed Matter Physics, 2001)
The equivalence of the asymptotic expression for the interaction energy between a pair of large hard spheres in a fluid of small hard spheres that has been obtained by Roth et al. [Phys. Rev. E, 2000, vol. 62, p. 5360] using Fourier transforms and an expression that we have obtained [J. Colloid Int. Sci., 1999, vol. 210, p. 320] using Laplace transforms is pointed out and commented upon.